2008
DOI: 10.1002/jgm.1203
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gene therapy using CTLA4Ig/silica‐nanoparticles on canine experimental autoimmune thyroiditis

Abstract: The CTLA4Ig-induced suppression of Th1 cytokines is relatively more significant than it appears because autoimmune thyroiditis is a Th1-polarized disease. Thus, CTLA4Ig can improve Th1/Th2 cytokine balance in autoimmune thyroiditis by downregulating Th1 cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Blockade of the B7/CD28 co‐stimulatory interactions with the soluble CTLA4Ig fusion protein has been shown to inhibit humoral immunity 20, graft rejection 21, 22, graft versus host disease 23, and to ameliorate autoimmune diseases 24 including experimental autoimmune encephalomyelitis, diabetes and collagen‐induced arthritis. In addition, we have shown in a previous canine study that gene therapy using CTLA4Ig gene/silica‐nanoparticles can improve Th1/Th2 cytokine balance in autoimmune thyroiditis 25.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Blockade of the B7/CD28 co‐stimulatory interactions with the soluble CTLA4Ig fusion protein has been shown to inhibit humoral immunity 20, graft rejection 21, 22, graft versus host disease 23, and to ameliorate autoimmune diseases 24 including experimental autoimmune encephalomyelitis, diabetes and collagen‐induced arthritis. In addition, we have shown in a previous canine study that gene therapy using CTLA4Ig gene/silica‐nanoparticles can improve Th1/Th2 cytokine balance in autoimmune thyroiditis 25.…”
Section: Introductionmentioning
confidence: 78%
“…In our previous gene therapy study using CTLA4Ig/silica‐nanoparticles in EAT dogs, we showed that CTLA4Ig can improve the Th1/Th2 balance in autoimmune thyroiditis by down‐regulating Th1 cytokines. CTLA4Ig‐induced suppression of Th1 cytokines is relatively more significant than it appears 25 because polarized Th1 responses predominate in autoimmune thyroiditis not only in the thyroid, but also in peripheral blood 4, 31–33.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, there have been many studies, which used various animal models of experimental thyroiditis to examine autoimmune disorders (Chen et al, 2009;Choi et al, 2008;Sundick et al, 1996;Tan et al, 2008). Some of these studies used bovine or human thyroglobulin immunization (Arata et al, 2006;Choi et al, 2008), or immunization with recombinant thyroid peroxidase (Ng et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…CTLA4Ig treatment elicited improvements in murine SLE, judging from the decrease in proteinuria and increase in survival (Finck et al, 1994). CTLA4Ig gene therapy also had beneficial effects on canine SLE (Choi et al, 2005) and canine experimental autoimmune thyroiditis (Choi et al, 2008). A phase III clinical trial using CTLA4Ig in human SLE is currently underway (Mok, 2010).…”
Section: Therapy Targeting B Cell-t Cell Interaction (Inhibition Of Cmentioning
confidence: 99%